Economic Evaluation for different Level of Agricultural Mechanization in Manipur - Singh, L. Kanta; Devi, S. Roma (Indian Journal of Hill Farming, 2017)
Agriculture is the mainstay of the state's economy with about 76 % of the working population in the state directly or indirectly depending on agriculture for employment and livelihood. Improved tools and equipments namely, paddy drum seeder, cono weeder and pedal operated paddy thresher were used in this study for different level of agricultural mechanisation. Improved mechanised farming could save more than 50% of the total cost involved in traditional farming. By using cono weeder for weeding of paddy cultivation could save Rs. 6560.00 per hectare over the manual weeding. Seed requirement using paddy drum seeder could reduce 50% over the traditional farming and also save Rs. 10830.00 per hectare in paddy nursery raising and transplantation over the traditional farming. Using pedal operated paddy thresher for threshing of paddy could save Rs. 3200.00 per hectare over the traditional farming and which are the major significant of mechanisation. The cost of cultivation of rice could be further reduced by mechanizing various activities involved in rice cultivation.